Pogled na delo in prispevek prof. dr. Jelke Šmid - Korbar k razvoju slovenske farmacevtsko-tehnološke stroke skozi oči farmacevtske industrije - Vrečer, Franc (Farmacevtski vestnik, 2024)
Professor Jelka Šmid - Korbar undoubtedly left a big mark on the Slovenian pharmaceutical profession and contributed to the development of many areas within the profession. her vision and extensive work in the research, educational fieldsand contributed to the development of Slovenian pharmaceutical industry.
Keywords: Farmacevtska industrija; indentifikacija nečistot; kortizol; Šmid-Korbar, Jelka; test ACTH; tetrakozaktid; vsebnik